Immunohistochemical expression of p16INK4a and bcl-2 according to HPV type and to the progression of cervical squamous intraepithelial lesions - Guimarães, Márcia C.M.; Gonçalves, Maria Alice G.; Soares, Christiane P.; Bettini, Jussara S.R.; Duarte, Roberta A.; Soares, Edson G. (SAGE Publications, 2005)
Inactivation of the cell cycle inhibitor gene p16MTS1 seems to be involved in human papillomavirus (HPV)-related carcinogenesis because E6 and E7 oncoproteins may impair p16INK4a and, indirectly, bcl-2 functions. In this study, we analyzed the role of immunohistochemical expression of p16 INK4a and bcl-2 in HPV-infected cervical biopsies as prognostic markers of the progression of squamous intraepithelial lesion (SIL). Sixty-five cervical biopsies were stratified into two subgroups according to the second biopsy: 27 of them maintained a low-grade (LG)-SIL diagnosis, and 38 progressed from LG-SIL to high-grade (HG)-SIL. p16INK4a and bcl-2 quantitative expression levels were measured by the immunoperoxidase method. PCR-DNA techniques were used to detect and type HPV. The Wilcoxon and Fisher exact tests were employed for the statistical analysis. In the group with an LG-SIL diagnosis at the second biopsy, no significant associations were found between p16INK4a and bcl-2 expression and presence of HPV16/18. In the group that progressed to HG-SIL, a significant association was observed between p16INK4a overexpression and HPV16/18 presence (p = 0.021), but none with bcl-2 levels. It is concluded that immunohistochemical bcl-2 expression may not be useful for predicting the progression of HPV-related SIL. In contrast, p16INK4a overexpression seemed to be associated with HPV 16 and 18, suggesting that it may be a good marker for predicting SIL progression.
Keywords: Bcl-2; Carcinogenesis; Human papillomavirus; p16INK4a; Squamous intraepithelial lesions